2013
DOI: 10.1155/2013/392058
|View full text |Cite
|
Sign up to set email alerts
|

In VitroAntibacterial and Antibiofilm Activities of Chlorogenic Acid against Clinical Isolates ofStenotrophomonas maltophiliaincluding the Trimethoprim/Sulfamethoxazole Resistant Strain

Abstract: The in vitro antibacterial and antibiofilm activity of chlorogenic acid against clinical isolates of Stenotrophomonas maltophilia was investigated through disk diffusion, minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), time-kill and biofilm assays. A total of 9 clinical S. maltophilia isolates including one isolate resistant to trimethoprim/sulfamethoxazole (TMP/SMX) were tested. The inhibition zone sizes for the isolates ranged from 17 to 29 mm, while the MIC and MBC values r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 30 publications
1
79
2
Order By: Relevance
“…Consistent with our results, caffeic acid content level decreased in hairy roots (661.50 μg/g) compared to nontransformed roots (715.25 μg/g). Previously demonstrated that chlorogenic acid and chlorogenic acid containing plant materials have been shown to have antiviral, antifungal, and strong antibacterial activities (Karunanidhi et al, 2013). Salicylic acid and gentisic acid were predominant hydroxybenzoic acid groups in hairy roots (999.00 and 758.15 μg/g) and non-transformed roots (741.00 and 553.85 μg/g) followed by gallic acid, p-hydroxybenzoic acid, syringic acid, protocatechuic acid, β-resorcylic acid and vanillic acid.…”
Section: Comparison Of Phenolic Compounds In Transgenic Hairy Roots Amentioning
confidence: 99%
“…Consistent with our results, caffeic acid content level decreased in hairy roots (661.50 μg/g) compared to nontransformed roots (715.25 μg/g). Previously demonstrated that chlorogenic acid and chlorogenic acid containing plant materials have been shown to have antiviral, antifungal, and strong antibacterial activities (Karunanidhi et al, 2013). Salicylic acid and gentisic acid were predominant hydroxybenzoic acid groups in hairy roots (999.00 and 758.15 μg/g) and non-transformed roots (741.00 and 553.85 μg/g) followed by gallic acid, p-hydroxybenzoic acid, syringic acid, protocatechuic acid, β-resorcylic acid and vanillic acid.…”
Section: Comparison Of Phenolic Compounds In Transgenic Hairy Roots Amentioning
confidence: 99%
“…Chlorogenic acid is a polyphenolic compound that forms an ester with caffeic acid with the 3-hydroxyl group of a quinic acid. It was demonstrated to have various health benefits including antiviral, antioxidant, antibacterial, antifungal, and other biological activities [13,14]. Furthermore, caffeic acid and chlorogenic acid were also found to be anticariogenic compounds [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Chlorogenic acid (3-O-caffeoylquinic acid), which is formed from caffeic and quinic acids is one of the major phenolic components seen in tobacco leaves and coffee seeds. Chlorogenic acid has multipharmacological properties such as antimicrobial 39 , anti-inflammatory effects 40,41 and cardioprotective effects 42,43 . It is a potent antioxidant, widespread in fruits and vegetables.…”
Section: Discussionmentioning
confidence: 99%